Concurrent benzodiazepine use in older adults treated with antidepressants in Asia. (7th December 2017) - Zhong, Xiao-Mei; Wang, Fei; Zhang, Qinge; Ungvari, Gabor S.; Ng, Chee H.; Chiu, Helen F. K.; Si, Tian-Mei; Sim, Kang; Avasthi, Ajit; Grover, Sandeep; Chong, Mian-Yoon; Chee, Kok-Yoon; et al.
ABSTRACT: Background: Little is known about the combined use of benzodiazepines and antidepressants in older psychiatric patients. This study examined the prescription pattern of concurrent benzodiazepines in older adults treated with antidepressants in Asia, and explored its demographic and clinical correlates. Methods: The data of 955 older adults with any type of psychiatric disorders were extracted from the database of the Research on Asian Psychotropic Prescription Patterns for Antidepressants (REAP-AD) project. Demographic and clinical characteristics were recorded using a standardized protocol and data collection procedure. Both univariate and multiple logistic regression analyses were performed. Results: The proportion of benzodiazepine and antidepressant combination in this cohort was 44.3%. Multiple logistic regression analysis revealed that higher doses of antidepressants, younger age (<65 years), inpatients, public hospital, major comorbid medical conditions, antidepressant types, and country/territory were significantly associated with more frequent co-prescription of benzodiazepines and antidepressants. Conclusions: Nearly, half of the older adults treated with antidepressants in Asia are prescribed concurrent benzodiazepines. Given the potentially adverse effects of benzodiazepines, the rationale of benzodiazepines and antidepressants co-prescription needs to be revisited.